Effects of Nicorandil Administration on Infarct Size in Patients With ST‐Segment–Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention: The CHANGE Trial - Geng Qian; Ying Zhang; Wei Dong; Zi‐Chao Jiang; Tao Li; Liu‐Quan Cheng; Yu‐Ting Zou; Xiao‐Si Jiang; Hao Zhou; Xin A; Ping Li; Mu‐Lei Chen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Nicorandil was reported to improve microvascular dysfunction and reduce reperfusion injury when administered before primary percutaneous coronary intervention. In this multicenter, prospective, randomized, double‐blind clinical trial (CHANGE [Effects of Nicorandil Administration on Infarct Size in Patients With ST‐Segment–Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention]), we investigated the effects of nicorandil administration on infarct size in patients with ST‐segment–elevation myocardial infarction treated with primary percutaneous coronary intervention. Methods and Results A total of 238 patients with ST‐segment–elevation myocardial infarction were randomized to receive intravenous nicorandil (n=120) or placebo (n=118) before reperfusion. Patients in the nicorandil group received a 6‐mg intravenous bolus of nicorandil followed by continuous infusion at a rate of 6 mg/h. Patients in the placebo group received the same dose of placebo. The predefined primary end point was infarct size on cardiac magnetic resonance (CMR) imaging performed at 5 to 7 days and 6 months after reperfusion. CMR imaging was performed in 201 patients (84%). Infarct size on CMR imaging at 5 to 7 days after reperfusion was significantly smaller in the nicorandil group compared with the placebo (control) group (26.5±17.1 g versus 32.4±19.3 g; P=0.022), and the effect remained significant on long‐term CMR imaging at 6 months after reperfusion (19.5±14.4 g versus 25.7±15.4 g; P=0.008). The incidence of no‐reflow/slow‐flow phenomenon during primary percutaneous coronary intervention was much lower in the nicorandil group (9.2% [11/120] versus 26.3% [31/118]; P=0.001), and thus, complete ST‐segment resolution was more frequently observed in the nicorandil group (90.8% [109/120] versus 78.0% [92/118]; P=0.006). Left ventricular ejection fraction on CMR imaging was significantly higher in the nicorandil group than in the placebo group at both 5 to 7 days (47.0±10.2% versus 43.3±10.0%; P=0.011) and 6 months (50.1±9.7% versus 46.4±8.5%; P=0.009) after reperfusion. Conclusions In the present trial, administration of nicorandil before primary percutaneous coronary intervention led to improved myocardial perfusion grade, increased left ventricular ejection fraction, and reduced myocardial infarct size in patients with ST‐segment–elevation myocardial infarction. Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT03445728.